Advancements in Multi-Channel SAW-Based UV Corona Sensor for Localizing and Positioning Corona Discharge Events in Power Facilities - Nawaz, Faisal; Lee, Hyunho; Choi, Cheol; Park, Jung Woong; Lee, Keekeun (2024 10th International Conference on Condition Monitoring and Diagnosis, CMD 2024, 2024)
The study presents the design, fabrication, and characterization of a novel 3-channel surface acoustic wave (SAW) UV corona sensor based on ZnO multilayer thin film structures. The primary objective of this study is to develop a sensor system capable of simultaneously detecting UV radiation from corona discharges at multiple locations. The SAW corona sensors were incorporated into a newly developed 3D-printed model, thereby facilitating the detection of simultaneous corona discharge events.
Keywords: Channel surface; Corona discharges; Fabrication and characterizations; Multi channel; Multi-layer thin film; Power; Surface acoustic wave sensors; Surface acoustic waves; ZnO; ZnO multilayer thin film; Corona discharge; SAW sensor; ZnO multilayer thin films